"At Wits' End!": Perspectives of Hispanic Caregivers of a Family Member with Schizophrenia. (1st June 2013) - Saunders, Jana
<x xml:space="preserve">Abstract</x> The purpose of this qualitative exploratory study was to explore the perspectives of Hispanic caregivers as they provide the day-to-day care for their family member with schizophrenia. Interviews were conducted by a promotora (a Spanish speaking trained community health worker) with ten Hispanic caregivers at a large community center in a southwest border city over a six month period. Sixty interviews were audio recorded, translated into English, transcribed, and then interpreted using content analysis. One main overarching perspective emerged: "at wits' end." The following four supportive themes emerged: feeling marginalized, seeking answers, relying on God, and lacking support.